Navigating English for Specific Purposes (ESP) in Morocco: Challenges, Opportunities, and Technological Integration - Youssefi, Imad (International Journal of Language and Literary Studies, 2024)
This study examines the perceptions and experiences of law and humanities students at the multidisciplinary faculty of Taza, Sidi Mohamed Ben Abdellah University, regarding English for Specific Purposes (ESP) education in Morocco. Using a mixed-methods approach, quantitative data from a survey of 130 students is complemented by qualitative insights from interviews and classroom observations. Findings reveal that 79% of respondents stress the need for ESP curricula tailored to their academic disciplines, with over 70% advocating for increased class frequency and interactive instructional methods. Challenges include technological limitations, such as compatibility issues with the Rosetta Stone application, and significant disparities in student proficiency levels, which complicate instruction in large, diverse classes. A gap in lesson adequacy is also noted between law and humanities students, underscoring the need for discipline-specific approaches. Recommendations include enhancing collaboration between language instructors and subject-matter experts, addressing logistical barriers, and improving technology integration. These measures aim to strengthen ESP programs in Morocco, equipping students with the skills needed for academic and professional success.